Impact of rural microfinance on rural poverty in Zimbabwe: the case of Mutasa District – 2010 to 2012. - Tarugarira, Dorcas (Midlands State University, 2015)
Microfinance has become a very important economic empowerment tool for reducing poverty across the globe. The assumption is that by improving access to credit, poor households will be able to set up micro enterprises that will generate income that is aimed at reducing poverty both at household and community levels. Literature has shown that informal microfinance models have become very popular with the rural population mainly due to their accessibility, affordability and community involvement. The major objective of this study was therefore to examine the role played by two microfinance models; ISAL and ROSCAs in reducing poverty. The study used Wards 4 and 30 of Mutasa District, Manicaland Province as a case study. ISAL and ROSCA participants and other key informants provided rich pooled data that informed the study findings. The researcher’s utilisation of the mixed methods approach provided strengths that offset the weaknesses of both qualitative and quantitative research. The study findings revealed that these two informal microfinance models have a significant positive impact on household poverty. Evidence of improved household income has been shown through increased access to health and education, quality food, accumulation of household and productive assets and livestock by participating households. The study has recommended a holistic and coordinated approach by policy makers and all relevant development practitioners that will create an enabling environment for informal microfinance to register more positive impact both at household and community levels.